Efforts of the Principal of MI in Facing the Challenges of Globalization through Character Strengthening - Azizah, Habibah Nur; Nugraha, Taufik Agung; Uswatussolihah, Siti Wifa; Suhendi, Saca; Sarbini (Research Horizon, 2025)
This research is motivated by the challenges of globalization that require Islamic educational institutions to be able to equip students with strong and competitive characters. The purpose of this study is to examine in depth the efforts of the principal of MI Cerdas Nurani in facing these challenges. The research used a qualitative approach with a case study method conducted at MI Cerdas Nurani, Cimahi City. Data collection techniques included interviews, group discussions, and observations, while data analysis was conducted descriptively and narratively. The research findings indicate that the principal’s main strategy in facing globalization is maintaining the sustainability of the Habit Character Life Skill (HCL) Curriculum. This curriculum focuses on strengthening the character of religious, independent, and competitive students through the habituation of the values ​​of cleanliness, neatness, and discipline, as well as the practice of daily worship and applicable monthly habits. Implementation is carried out through stages of habit campaigns and habit celebrations by involving the active role of parents and the role models of the principal and teachers. The HCL Curriculum is a strategic innovation of the principal of MI Cerdas Nurani in fortifying students from the negative impacts of globalization while preparing them to compete globally.